PERANAN SEKTOR NON PERTANIAN TERHADAP PENDAPATAN RUMAH TANGGA PETANI BERLAHAN SEMPIT - NURMANAF, A. ROZANY (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 4, No. 3 November2004, 2012)
The objective of study is to identify non agricultural sector role on household income sources of small sized cultivating farmers. By direct interview, data collected in covering househld income structure by elevation, agroecosystem and accessibility of the region. Analysis shows that the role of non agricultural sector is dominant in low land area with the agroecosystem paddy field which has a good physical accessibility. Although the activities in the region vary, the important contribution on household income are limited just on several activities, like trading, non agricultural labour and money sending from the household member who work outside of the region. That’s why household income in this area, dominantly supported by the activities which have skill and capital. On the other hand, in high land area with agroecosystem of dry land and bad accessibility, non agricultural activities are limited. Household income of small sized cultivating farmers are dominated by the contribution of agricultural sector activities which include paddy field farming system, dry land farming system, agricultural labour and livestock farming system. As a source of income, non agricultural activities are limited, just came from the activities which have low labour productivity. Consequently, income level of society in the region are lower.
Keywords: Regional Elevation, Agroecosystem, Accessibility, Agricultural Sector, Non Agricultural Sector